1996
DOI: 10.1302/0301-620x.78b3.0780452
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Patellar Tendonitis

Abstract: The radiological and MRI appearances of 24 knees with patellar tendonitis resistant to conservative therapy were analysed to identify the characteristic MRI appearance and to determine if the patellar morphology was abnormal. A significant thickening of the tendon was found in all cases; this was a more reliable diagnostic feature than a high signal within the superior posterior and central aspect of the tendon at its proximal attachment The site of the lesion shown by MRI is more compatible with impingement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
116
1
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(135 citation statements)
references
References 19 publications
11
116
1
6
Order By: Relevance
“…17 Likewise, both maximum point strain and mean localized strain significantly increased with increasing applied patellar tendon strain.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…17 Likewise, both maximum point strain and mean localized strain significantly increased with increasing applied patellar tendon strain.…”
Section: Discussionmentioning
confidence: 91%
“…17 While the excessive tensile loading is thought to induce microscopic tears within the tendon, ultimately leading to degeneration, 19,34,38,39 the suggested pathogenesis of stress overload and tensile failure has, to date, not been able to explain why the lesion of patellar tendinopathy is localized to the proximal portion of the patellar tendon at its insertion to the inferior pole of the patella. 17 Cadaveric studies examining the surface strains of the patellar tendon through the range of motion have produced conflicting results. 1,5 One group found that on flexion, the tensile strain on the patellar tendon increased on the anterior aspect of the tendon and decreased on the posterior aspect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hipótese de que o pólo inferior da patela pode influenciar o aparecimento da tendinopatia patelar foi reforçada com a existência de um pólo inferior longo da patela em pacientes com tendinopatia patelar (18)(19)(20) . Porém, o pólo inferior da patela longo pode, em verdade, representar um osteófito de tração, causado por determinada força de alta tensão repetitiva e pode não ser uma anormalidade preexistente que contribuiu para a tendinopatia patelar (19) .…”
Section: Etiologiaunclassified
“…Laduron et al 33 suggested that there might be an impingement between the deep fi bers of the proximal patellar tendon and the lateral part of the femoral trochlea during full extension. Johnson et al, 34 however, found confl icting results in a magnetic-resonance-imaging study. They found suggestion of this impingement during knee extension in only 2 of the 24 knees they studied and therefore discounted Laduron's theory.…”
Section: Etiologymentioning
confidence: 97%